Pengaruh Pendidikan Kesehatan Tentang Inspeksi Asam Asetat (IVA) Terhadap Motivasi Wus dalam Deteksi Kanker Serviks di Puskesmas Putri Ayu Jambi - Hesty Hesty; Rahmah Rahmah; Nurfitriani Nurfitriani (Universitas Batanghari Jambi, 2019)
World Health Organization (WHO), cervical cancer is the number two cause of death in the world for women from all existing cancer. Every two minutes a woman dies of this disease. This cancer attack at an early stage does not cause any symptoms. That is why, why does this type of cancer fall into the category of the silent killer. One of the promotive and preventive efforts in women of childbearing age as primary prevention can be through the provision of health education about cervical cancer using the Acetic Acid Inspection (IVA) method. The purpose of this study is to find out whether there is an influence of health education about IVA on WUS motivation in cervical cancer detection in health centers. Putri Ayu Jambi. This type of quantitative research with non randomized pretest-posttest with control group design, with purposive sampling technique totaling 22 WUS, 11 people as controls and 11 experimental people. The instrument in the form of questionnaires was analyzed by univariate and bivariate Paired Test t-test, which was conducted from April to July 2018. The results of the study revealed that of the 22 WUSs studied, the average motivation of the pretest in the experimental group was 41.1818 and the control group was 39.9091, while the results of the posttest of the experimental group after being given counseling and leaflets increased by 42.9091 with p-value 0.034. There is an influence of health education about IVA tests on WUS motivation in detecting cervical cancer. It is suggested that the Puskesmas can improve activities in planning disease control programs, especially carrying out counseling and counseling both in the puskesmas building and in the working area of the puskesmas by involving cadres in their environment so that WUS is moved to take the IVA examination.